Education Behind the Wall : Why and How We Teach College in Prison - Gellman, Mneesha (Book collections on Project MUSE., 2022)
"This edited volume seeks to address some of the major issues for faculty teaching college classes to incarcerated students. It is composed of a series of case studies showcasing the strengths and challenges of teaching in prison as well as honest reflection on the reality of education in a constrained environment"--